IgG4-Related Hypophysitis: A New Addition to the Hypophysitis Spectrum - Leporati, Paola (Endocrine Society, 2011)
CONTEXT: Hypophysitis is a chronic inflammation of the pituitary gland that comprises an increasingly complex clinicopathological spectrum. Within this spectrum, lymphocytic and granulomatous hypophysitis are the most common forms, but newer variants have recently been reported. OBJECTIVE: The aims of the study were to describe a new patient with IgG4-related hypophysitis, review the published literature, and provide diagnostic criteria. SETTING: A 75-yr-old man presented with a 1-yr history of frontal headache. Initial studies revealed panhypopituitarism and a mass in both the sella turcica and the sphenoidal sinus. The patient underwent transphenoidal surgery, initiated high-dose prednisone followed by hormone replacement therapy, and was closely monitored for 3 yr. RESULTS: Symptoms improved after prednisone, along with shrinkage of the pituitary and sphenoidal masses, but recurred when prednisone dose was lowered. Histopathology showed a marked mononuclear infiltrate in both the pituitary and sphenoidal specimens, mainly characterized by increased numbers of plasma cells. Many of the infiltrating plasma cells (>10 per high-power field) were IgG4-positive. Review of the literature identified 11 cases of IgG4-related hypophysitis (two diagnosed based on pituitary histopathology). CONCLUSIONS: We describe the first Caucasian patient with biopsy-proven IgG4-related hypophysitis and provide classification criteria for this disease.